2019
DOI: 10.1021/acs.orglett.9b03209
|View full text |Cite
|
Sign up to set email alerts
|

Toward Chromanes by de Novo Construction of the Benzene Ring

Abstract: The work describes three principal Diels–Alder cycloaddition approaches toward chromanes that are designed for the de novo construction of the benzene ring. This study specifically focuses on the potential exploitation in the total synthesis of chromane-bearing natural products such as cebulactam A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Interestingly, N-methyl indole derived chalcone 4l′ in reaction with 2a at 85 °C delivered the eliminated product 5ac′ exclusively in 57% yield. Similarly, alkynol 2g (obtained from (S)-pyroglutamic acid) 3 in reaction with sterically hindered chalcone 4k furnished tricyclic lactam fused N, O-heterocycle E5gk (confirmed by X-ray analyses) in 40% yield (Scheme 3, entry c); this unusual formation of heteroarene/arene eliminated products could be due to the stereoelectronic effect-driven competitive Grob-type elimination pathway 5,18 instead of classical oxidative aromatization (vide infra) (Scheme 3, entry c).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, N-methyl indole derived chalcone 4l′ in reaction with 2a at 85 °C delivered the eliminated product 5ac′ exclusively in 57% yield. Similarly, alkynol 2g (obtained from (S)-pyroglutamic acid) 3 in reaction with sterically hindered chalcone 4k furnished tricyclic lactam fused N, O-heterocycle E5gk (confirmed by X-ray analyses) in 40% yield (Scheme 3, entry c); this unusual formation of heteroarene/arene eliminated products could be due to the stereoelectronic effect-driven competitive Grob-type elimination pathway 5,18 instead of classical oxidative aromatization (vide infra) (Scheme 3, entry c).…”
Section: Resultsmentioning
confidence: 94%
“…12 Recently, Liu and Feng's, and Xu's research groups disclosed the participation of cyclic enol ethers (T1 and T2) as dienophiles in the inverse-electron demand hetero-Diels-Alder (IED-HDA) reaction with β-γ-unsaturated α-ketoesters 3 to give spiroketals P1 or fused acetals P2 under catalyst dependent conditions (Scheme 1, entry a). 13 In contrast to these findings, we previously reported that 4-pentyn-1-ols 1 would react with α-ketoesters or β-γ-unsaturated α-ketoesters 3 to deliver [5,5]oxaspirolactones P3, 14 and 5-hexyn-1-ols 2 would undergo [3 + 2] annulation with 3 to give furopyranones 15 P4 instead of IED-HDA adducts (P1, P2) under Bi(III) and Ag(I) or Au(I)-Ag(I)catalysis respectively. These distinct results could be attributed to the act of cyclic enol ethers (T1 and T2) as enolizable carbonyl equivalents under specific catalytic conditions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…All hydrogen atoms were readily located in difference Fourier maps and were subsequently treated as riding atoms in geometrically idealized positions with U iso (H) = kUeq(C,N), where k = 1.5 for NH and methyl groups, which were permitted to rotate but not to tilt, and 1.2 for all the other H atoms. In endo-3b atoms C9-C10 and C24 in each ethoxy group were disordered over two positions with the refined ratios 0.805 (19):0.195 (19) and 0.444(11):0.556 (11), respectively. Atoms C9A, C9B, C10A and C10B were refined with restrained U ij components.…”
Section: X-ray Single Crystal Analysismentioning
confidence: 99%
“…For example, in the case of cycloaddition between a substituted 3-acylamino-2H-pyran-2-one and ethyl vinyl ether [17] (or any other suitable alkene dienophile), in the first step a carbon-dioxide bridge system (i.e., 7-oxabicyclo[2.2.2]octene) is formed, such systems (including those formed via other reaction pathways) are known from the literature, but their solid-state structures were described just in a few cases, for some recent examples see ref. [18][19][20][21][22][23][24][25][26][27][28]. However, 7-oxabicyclo[2.2.2]octenes produced as described above can be formed as two possible regioisomers and each of these can exist as a mixture of two diastereoisomers (endo or exo), in turn each of the four distinctive possibilities is actually composed of a pair of enantiomers.…”
Section: Introductionmentioning
confidence: 99%